Effect of macro-design in the primary stability of short and extra-short implants using resonance frequency analysis. An ex vivo study - Ramón Silva; Pablo Villalón; Felipe Cáceres (Journal of Oral Biology and Craniofacial Research)
Objective: This study aimed to determine the effect of macro design in the primary stability of short and extra-short implants using resonance frequency analysis (RFA). Material and methods: On an ex-vivo model using pig's ribs, we inserted 80 short and extra-short dental implants (20 implants per brand): Biohorizons®(B) 4.6 × 6mm; Intralock®(I) 4.75 × 6.5 mm; Straumann®(S) 4.1 × 4mm; and Tixos®(T) 5 × 5mm. Primary implant stability was measured using an RFA device. We compared mean ISQ values through ANOVA test. Results: Mean ISQ values: B = 73.36 (±3.39); I = 75.13 (±3.88); S = 65.38 (±8.38); T = 72.13 (±11). B and I showed higher ISQ than S (p-value < 0.001). Short (I) showed higher ISQ than extra-short (B,S,T) implants (p-value = 0.001). Tapered (B,I) had higher ISQ than parallel (S,T) implants (p-value < 0.001). There was a moderate positive correlation between ISQ and length (r = 0.52), and a weak correlation with diameter (r = 0.33). Discussion: The final result is a combination of implant design, length, and diameter. Tapered design (B and I) and larger implants (I) showed better primary stability in terms of ISQ values. This information could be beneficial at implant selection in a severely reabsorbed low-quality bone, privileging length (as long as it is safe), and conical walls design.